Pengaruh Brand Communication, Brand Evidence, Dan Gamification Terhadap Loyalitas Merek Dengan Kepuasan Konsumen Sebagai Intervening - Suratman, Richo E (Universitas Sam Ratulangi, 2018)
The purpose of this research is to analyze the effect of brand communication, brand evidence, and gamification on consumer satisfaction and brand loyalty, then test the role of customer satisfaction as a mediator in the relationship between brand communication, brand evidence and gamification on brand loyalty in Starbucks Manado Town Square. The amounts of sample are 100 respondents by using purposive sampling method where the respondent are required to have or currently using Starbucks app. The research showed that brand evidence and gamification directly have a positive and significant effect on brand loyalty. Then brand communication and brand evidence have a significant positive effect on customer satisfaction. While brand communication does not have positive and significant effect on brand loyalty, as well as gamification does not have positive and significant effect on customer satisfaction. Customer satisfaction has no significant effect as an intervening or mediating on brand loyalty nor does it have a positive and significant effect directly on brand loyalty.Keywords: Brand Communication, Brand Evidence, Gamification, Consumer Satisfaction, Brand Loyalty